PENGARUH DISIPLIN BELAJAR TERHADAP KESULITAN BELAJAR EKONOMI SISWA KELAS X SEKOLAH BERASRAMA DI KOTA PADANG PANJANG - Febri Hastuti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Abstract The aims of this study are to analyze learning discipline that influence students learning difficulties of economics grade X at boarding schools in Padangpanjang. The type of this research is explorative research. The techniques of data analysis was done by using Wald Test and Chi Square at significance level 5%. Based on the finding and analysis of the data it can be concluded that third factors have significant influence in learning difficulties. Keywords: disiplin belajar, kesulitan belajar.